Polytopic linear parameter varying model-based tube model predictive control for hypersonic vehicles. (22nd June 2017) - Hu, Chaofang; Yang, Na; Ren, Yanli
This article investigates a tube model predictive control scheme ensuring robustness and constraints fulfillment for hypersonic vehicles with bounded external disturbances. The polytopic linear parameter varying model is established using tensor-product modeling method, and tube-model predictive control controller is designed to satisfy all vertices of the polytopic linear parameter varying model. Firstly, the nominal model predictive control law is constructed for the nominal system without disturbances. Secondly, tube invariant set strategy is introduced for the unknown bounded disturbances, and the local robust feedback control law is presented to restrain disturbances. The proposed tube-model predictive control method not only steers the nominal state to track a reference trajectory but also keeps the real states within a tube centered with the nominal trajectory. Simulation results show the effectiveness of the proposed method for the hypersonic vehicle with bounded disturbances.